2023
DOI: 10.21203/rs.3.rs-3034274/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular switching in transcription through splicing and proline-isomerization regulates stress responses in plants

Frederik Theisen,
Andreas Prestel,
Steffie Elkjær
et al.

Abstract: The Arabidopsis thaliana DREB2A transcription factor interacts with the negative regulator RCD1 and the ACID domain of subunit 25 of the transcriptional activator mediator (Med25) to integrate stress signals for gene expression, with elusive molecular interplay. Using biophysical and structural analyses together with high-throughput screening, we revealed a bivalent binding switch in DREB2A containing a novel ACID-binding motif (ABS) and the RCD1-binding motif (RIM). The RIM is lacking in a stress-induced DREB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…7). During the revision of our manuscript, an independent biophysical analysis of AtMED25 ACID domain in complex with AtDREB2a became available [65]. Our results with AtDREB2a (252–277) are in good agreement with the NMR, ITC, MD, and AlphaFold experiments performed in this study with a longer AtDREB2a fragment (234–276).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…7). During the revision of our manuscript, an independent biophysical analysis of AtMED25 ACID domain in complex with AtDREB2a became available [65]. Our results with AtDREB2a (252–277) are in good agreement with the NMR, ITC, MD, and AlphaFold experiments performed in this study with a longer AtDREB2a fragment (234–276).…”
Section: Discussionsupporting
confidence: 83%
“…Our results with AtDREB2a (252–277) are in good agreement with the NMR, ITC, MD, and AlphaFold experiments performed in this study with a longer AtDREB2a fragment (234–276). In particular, the authors identified two AtMED25 ACID binding motifs in AtDREB2a (234–276) [65], one of which corresponds to the one we have just highlighted in this study. However, the predicted AtMED25 binding interface appears swapped between AtDREB2a (252–277) and AtDREB2a (234–276) [65], underlining once more the importance of choosing carefully the right delimitations to optimize the accuracy of AlphaFold predictions [59,66].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our results with AtDREB2a (252-277) are in good agreement with the NMR, ITC, MD and AlphaFold experiments performed in this study with a longer AtDREB2a fragment (234-276). In particular, the authors identified two AtMED25 ACID binding motifs in AtDREB2a (234-276) (60), one of which corresponds to the one we have just highlighted in this study. Additional AlphaFold Arabidopsis MED25 ACID domain/TADs models to guide experimental studies will help elucidate how sequences divergence between orthologs may play a role in dictating molecular recognition.…”
Section: Discussionsupporting
confidence: 61%
“…The predicted shared binding interface located at the top of the β-barrel core, led us to hypothesize that hMED25 and AtMED25 ACID are structurally conserved (Figure 1) but that AtMED25-TADs interactions are specific to plants (Figure 7). During the preparation of our manuscript, an independent biophysical analysis of AtMED25 ACID domain in complex with AtDREB2a became available (60). Our results with AtDREB2a (252–277) are in good agreement with the NMR, ITC, MD and AlphaFold experiments performed in this study with a longer AtDREB2a fragment (234–276).…”
Section: Discussionmentioning
confidence: 99%